Recuperação de potássio da rocha verdete via reação com hidróxido de cálcio em condições hidrotermais - Peixoto, Rodrigo de Almeida Oliveira (2019)
Ensuring quality food, and in sufficient quantities, is a global challenge. The use of fertilizers is of fundamental importance, since it promotes the increase of agricultural yield of poor productive soils. Brazil has enormous agricultural potential, but due to soil conditions, it needs large amounts of fertilizer. Despite the high demand, domestic production is not sufficient to meet consumption and needs to resort to imports. Regarding potassium fertilizers, the country currently imports about 90% of its total demand. Potash evaporitic deposits are the main sources of K, but besides having few deposits, Brazil has only one mine in operation: Taquari Vassouras/SE. Verdete, a silicate rock that has considerable potassium content, is an alternative source for obtaining the element. This work aims to analyze the efficiency of K recovery from Verdete through reaction with calcium hydroxide under hydrothermal conditions. The obtained solid products were characterized by X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). K extraction was performed in the presence of citric acid and water, with subsequent analysis by flame photometry. The products were filtered, and the filtered and retained fractions were characterized aiming to determine the crystalline structures that compose them. The results showed that the reaction between Verdete and calcium hydroxide begins to occur effectively after 2 h, and that release of K+ occurred mainly due to breakdown of K-feldspar lattice. The solid fraction of hydrothermal products is composed mainly of hibschite and tobermorite. In filtered products, the soluble phase consists mainly of calcium carbonate in calcite and aragonite forms. Finally, the results showed that citric acid promoted higher potassium extraction than water. This implies that, after the hydrothermal procedure, even if the element has already been extracted from the crystal lattice of K-feldspar, K+ ions still interact with the remaining solid in an unknown way, but treatment with acid solution enables its final extraction into the liquid phase.